BUDGETING INFORMATION SYSTEM DESIGN IN iFRAMES: CASE STUDY ON HEALTH SECTOR BLUD - Budiman Linggo Santoso; Machmudin Eka Prasetya (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2018)
At the moment, budgeting processes carried out in Regional Public Service Agency in health sector in DKI Jakarta had been done manually so changes between corrective Work Plan and Budget (RKA)s and updated RKA cannot be seen directly. It causes ineffectiveness and bad transparency in the budget preparation process as unconfirmed RKAs are not well documented. The purpose of this study is to create a design of integrated accounting information system between budgeting information system as a part of Integrated Financial Reporting and Management Information System (iFRAMES). Transparency Theory is used to analyze the needs of budgeting transparency in government organization. The method used in budgeting system design is Framework for the Application of Systems Thinking (FAST) as the method in planning system design and the study approach used is a case study with triangulation method with qualitative data in the form of data from interview and quantitative data in the form of document review. The unit of analysis examined in this study is multiple-embedded units, between DKI Jakarta Health Office and BLUD. This study resulted in an integrated planning system design for BLUD to support planning activities so planning activities could be carried out with high transparency and efficiency.Keywords: Accounting Information System, BLUD, Budgeting System, FAST, Puskesmas, RKA, Theory of Transparency.